Inquiry Learning Worksheet to Strengthen Science Process Skills in Elementary Students - Huznul Hatima Rudi; Wawan Krismanto; Ila Israwaty (Walada: Journal of Primary Education, 2026)
Science instruction should facilitate the development of science process skills. Therefore, innovative teaching tools are needed; one of them is meaningful worksheets. This study aims to develop LiveWorksheets based on the inquiry learning model to facilitate the development of science process skills in fourth-grade elementary school students. This study uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Data were collected through observation, interviews, and questionnaires to assess the validity and practicality of the product and were analyzed descriptively, qualitatively, and quantitatively. The results of the needs analysis indicate that teachers and students need different, challenging worksheets. After a series of stages, the product was successfully designed and developed by integrating inquiry-based learning. These Liveworksheets present a variety of contextual, inquiry-based experiments, thus being useful for facilitating students' science process skills. Validity tests conducted by subject-matter and media experts indicate a highly valid category, while practicality tests conducted by teachers and students indicate a highly practical category. This research provides an important contribution to the development of technology-based science learning in elementary schools, particularly in facilitating students' science process skills through interactive worksheets.